The mechanisms and kinetics of phosphate adsorption onto iron‑coated waste mussel shell observed from hydrodynamic column - Fulazzaky, M. A.; A. Salim, N. A.; Khamidun, M. H.; Puteh, M. H.; M. Yusof, A. R.; Abdullah, N. H. L.; Syafuddin ·, A.; Zaini, M. A. A. (Springer, 2022)
The excessive amount of phosphate in domestic wastewater treatment plant efuent must be removed to protect the natural environment of healthy aquatic ecosystem. Though a number of adsorption techniques with various low-cost adsorbent have been proposed, it is still ambiguous how the iron-coated waste mussel shell properties afect the adsorption kinetics of phosphate removal from an efuent. The analysis of experimental data was carried out using the bed depth service time, Thomas, and modifed mass transfer factor models to study the adsorption kinetics of phosphate deposited on the surface of iron-coated waste mussel shell observed from hybrid plug fow column reactor. The overall adsorption kinetics of phosphate investigated using the Ka and No values referred to the bed depth service time models and the KT and qo values referred to the Thomas models are still acceptable. Detailed analysis of the mechanisms of flm mass transfer and porous difusion using the modifed mass transfer factor models is able to determine the kinetic rate of phosphate adsorption. Mass transfer resistance for the adsorption of phosphate onto iron-coated waste mussel shell from domestic wastewater treatment plant efuent is dependent on porous difusion ultimately contributing to develop advanced iron-coated waste mussel shell adsorbent for enhancing the performance of hybrid plug fow column reactor in future.